Keengganan Dayah Konservatif Berintegrasi dengan Kemodernan - Rizal, Syamsul; Pratiwi, Indah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
This study aims to determine the factors that cause conservative dayah to be reluctant to integrate and adapt to the modern era. Various reasons underlie the reluctance of conservative dayah to incorporate modern elements into their educational institutions, including fears and concerns about the fading of Islamic values and teachings which have become the basis of educational learning in dayah, the traditions of the salaf which are considered close to the habits of the prophet and the scholars will disappear and replace modern habits that are far from Islam, negative doctrines that develop in the modern era such as individualism, consumptive, capitalist, materialistic attitudes will become the basis of santri thinking that can damage the order of Islamic society. The negative impact of technological advances which are part of modernity is also a separate consideration for conservative dayahs not to include elements of modernity in the dayah environment. Qualitative research in this conservative dayah revealed that the dayah has imposed restrictions on the entry of modernity, including prohibiting the use of smartphones, the internet, and other technological tools in the learning process and the daily lives of santri while in the dayah, the non-use of modern education systems such as the use of uniforms, school entrance tests, the existence of general learning, the use of moderate Islamic books and other general books, being a form of rejection and unwillingness of dayah to integrate with modernity.